U.S. Army intelligence and interrogation handbook (Skyhorse Publishing, 2014)
Provides doctrinal guidance, techniques, and procedures governing the use of interrogators as human intelligence collection agents in support of a commander's intelligence needs. This book outlines the interrogator's role within the greater intelligence effort as well as the unit's day-to-day operations.